2012
DOI: 10.1371/journal.pntd.0001462
|View full text |Cite
|
Sign up to set email alerts
|

Human and Canine Echinococcosis Infection in Informal, Unlicensed Abattoirs in Lima, Peru

Abstract: Echinococcus granulosus infections are a major public health problem in livestock-raising regions around the world. The life cycle of this tapeworm is sustained between dogs (definitive host, canine echinococcosis), and herbivores (intermediary host, cystic hydatid disease). Humans may also develop cystic hydatid disease. Echinococcosis is endemic in rural areas of Peru; nevertheless, its presence or the extension of the problem in urban areas is basically unknown. Migration into Lima, an 8-million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
2
13
0
3
Order By: Relevance
“…Humans may also develop the disease, and hydatid cysts have been reported in several body organs, primarily the liver, lungs, and the retroperitoneal region [22]. Transmission of hydatid cysts in unlicensed abattoirs to neighboring people has been reported elsewhere [23]. Some dressing activities at slaughterhouses can reduce contamination of carcasses, but others still jeopardize carcass hygiene [24].…”
Section: Discussionmentioning
confidence: 99%
“…Humans may also develop the disease, and hydatid cysts have been reported in several body organs, primarily the liver, lungs, and the retroperitoneal region [22]. Transmission of hydatid cysts in unlicensed abattoirs to neighboring people has been reported elsewhere [23]. Some dressing activities at slaughterhouses can reduce contamination of carcasses, but others still jeopardize carcass hygiene [24].…”
Section: Discussionmentioning
confidence: 99%
“…A second study in the same area reported 46% (23/50) of dogs positive on coproantigen testing while 38% (13/34) of sheep were infected at postmortem examination (Moro et al, 1999). A study on abattoir workers and stray dogs from a nonendemic coastal city found 4 of 22 dogs positive while 3 of 32 human had liver CE (Reyes et al, 2012). Between 2009 and 2012, official data reported infection prevalence ranges of 3.61e 6.12% for cattle and 6.55e10.44% for sheep (PAHO, 2015).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 96%
“…In Canchayllo, a locality in the Peruvian highlands, ultrasound surveys detected CE in 4.9% of 309 subjects (Moro et al, 2005). Autochthonous transmission of E. granulosus occurs in Lima, based on findings of CE in 3/32 workers in unlicensed abattoirs, using a combination of abdominal ultrasound, chest X-rays and serology (Reyes et al, 2012). p0875…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…We cannot rule out entirely a more recent infection, since migration patterns and transport of animals can establish foci of infection in apparently nonendemic cities. 20 To date, there are only 11 other cases of laparoscopically treated spleen cysts reported (Table 1). [11][12][13][14][21][22][23][24][25][26][27] In these cases, the diagnosis of splenic CHD was based on imaging findings, complemented by positive serology in only three of them.…”
Section: Discussionmentioning
confidence: 99%